PERLINDUNGAN HUKUM ATAS ADAT PERNIKAHAN ETNIS MELAYU BATU-BARA SEBAGAI EKSPRESI BUDAYA TRADISIONAL MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA. - MUHAMMAD AKBAR (PREMISE LAW JURNAL, 2017)
ABSTRACT A traditional work is the result of thought or idea , Article 38 of Law No. 28/2014 on Copyright has its title, “Traditional Cultural Expression and Copyright of Unknown Inventor.”The research used juridical empirical and descriptive analytical The samples were taken by using snowball sampling technique. The result of the research showed that legal protection for the expression of traditional culture is stipulated in Law No. 28/2014 on Copyright which is based on the of Article 38, of Law No. 28/2014. What it means by “traditional cultural expression” is the effort of the community to protect the traditional cultural expression such as registering the Melayunese traditional marriage as one of traditional cultural expressions, increasing the quality of human resources in conserving Adat and Culture which has been a heritage from generation to generation, adjusting various customs and traditions to the age development without abandoning or changing them, continuously taking care of the Batubara Melayunese traditional marriage. The reasons why the Batubara Melayunese have not yet registered their traditional marriage are first, their ignorance about Law No. 28/20124 on Copyright; secondly, they are not legally aware of registering copyright on traditional marriage; thirdly, there is no seriousness of the Government apparatus in the registration of copyright about the traditional cultural expression of traditional marriage. Keywords: Protection, Traditional Cultural Expression